The changing shape of English nonconformity, 1825-1925 - Johnson, Dale A., 1936- (New York, N.Y. : Oxford University Press, 1999)
This book addresses several dimensions of the transformation of English Nonconformity over the course of an important century in its history. It begins with the question of education for ministry, considering the activities undertaken by four major evangelical traditions (Congregationalist, Baptist, Methodist, and Presbyterian) to establish theological colleges for this purpose, and then takes up the complex three-way relationship of ministry/churches/colleges that evolved from these activities. As author Dale Johnson illustrates, this evolution came to have significant implications for the Nonconformist engagement with its message and with the culture at large.
These implications are investigated in chapters on the changing perception or understanding of ministry itself, religious authority, theological questions (such as the doctrines of God and the atonement), and religious identity.
"Factories of Preachers and Pastors": The Nonconformist Engagement with Theological Education -- Modest Beginnings -- Evaluation and Reform -- The Methodist Quest for an Educated Ministry -- Piety, Education, and Ministry -- Ministry and Theology in a New Age: The Nonconformist Engagement with Its Message and with the Culture -- The Ministry Required by the Age -- The Shifting Sands of Religious Authority -- Theology and the Task of Reconstruction -- Nonconformity and Identity: Beyond the Chilling Mists of Controversy.
Includes bibliographical references (pages 223-241) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Dissenters, Religious -- England -- History -- 19th century; Theology -- Study and teaching -- England -- History -- 19th century; Dissenters, Religious -- England -- History -- 20th century; Theology -- Study and teaching -- England -- History -- 20th century; Dissidents (Religion) -- Angleterre -- Histoire -- 19e siècle.; Théologie -- Étude et enseignement -- Angleterre -- Histoire -- 19e siècle.; Dissidents (Religion) -- Angleterre -- Histoire -- 20e siècle.; Théologie -- Étude et enseignement -- Angleterre -- Histoire -- 20e siècle.; RELIGION -- Christianity -- Protestant; Dissenters, Religious; Theology -- Study and teaching; England; Dissenters; Theologie; Theologiestudium; Dissenters; 1800-1999; Geschichte 1825-1925.; Electronic books; History